Recent studies on increasing transdermal delivery systems of skin medicinal products - Neculai, Ana-Maria; Cima, Luiza-Madalina (Eximia, 2022)
The last decade has shown a growing interest in the topical use of natural substances, as an alternative to oral or systemic therapy, being proposed and investigated various classical and modern release systems capable of transporting and releasing the active substance more efficiently, thus optimizing its action therapeutic. Transdermic administration is an attractive alternative that reduce the oral administration of drugs or hypodermic injections. The biggest challenge for transdermic delivery systems is that only a limited number of drugs can be administered this way. Using current methods of administration, approved transdermic drugs have molecular weights that are close to several hundred Daltons, exposing the octanol-water partition coefficients that promote lipid formation, which requires the application of milligram doses per day. For more than a decade, research into the percutaneous pathway to facilitate hydrophilic absorption of drugs has been particularly difficult, and transdermic absorption of peptides and macromolecules, including the new genetic treatment using low-interference DNA or RNA, has created huge challenges. In this regard, this article highlights the progress of world medicine for different approaches to formulations, such as: iontophoresis, electroporation, thermal ablation, microneedles, non-cavitative ultrasound, microdermabrasion, the use of combinations of chemicals to enhance skin absorption and so on, in order to improve the skin penetration of topical pharmaceutical forms.